Identifikasi Pemanfaatan Beasiswa PIP dan Dampaknya terhadap Motivasi Berprestasi Serta Disiplin Siswa Penerima Beasiswa di SMA Pesisir Berau : (Study Kasus di SMAN 14 Berau) - Endry Setiawan; Widyatmike Gedhe Mulawarman; Evy Hanifah; Nur Khayati; Risna Herjayanti; Lailan Sawiyah Siagian; Mulyati Mulyati; Ami Aulia; Noryani Noryani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study aims to identify the utilisation of the Smart Indonesia Programme (PIP) scholarship and its impact on the achievement motivation and discipline of scholarship recipients at SMA Pesisir Berau. The research method used is qualitative with a case study approach. The research was conducted on 14 April - 24 April 2024 This case study was conducted at SMAN 14 Berau. The research subjects were 10 students who received PIP scholarship. Data were collected through unstructured interviews with 10 samples of students, parents, and counselling teachers. The results showed that; (1) The scholarship was utilised to buy school needs, transport costs, and help with family economic needs. (2) Scholarships have a positive impact on students' achievement motivation and discipline. (3) Factors that support the utilisation of scholarships and their positive impact are students' internal motivation, the role of parents, and school supervision.